Improving Thulium Fiber Laser Lithotripsy Efficiency - Hardy, Luke Allen (The University of North Carolina at Charlotte, 2018)
Kidney stone disease affects approximately 10% of the U.S. population. Conventional Holmium:YAG infrared laser lithotripsy is a standard minimally invasive treatment that operates based on a photothermal interaction with the main chromophore in tissue being water. Our laboratory is exploring the Thulium Fiber laser (TFL) as an alternative to Ho:YAG laser for lithotripsy, due to the TFL’s ability to operate at low pulse energies and high pulse rates, producing smaller stone fragments and reduced retropulsion. The TFL also more closely matches a high temperature water absorption peak. Additionally, the improved TFL spatial beam profile enables coupling of laser energy into smaller fibers (50-150-µm-core) than currently used in Ho:YAG lithotripsy. TFL ablation rate, ablation threshold, operation time, and vapor bubble dynamics and pressure transients were analyzed and compared to the Ho:YAG laser in all experiments. TFL ablation rate was examined at pulse rates up to 500 Hz. Ablation rates scaled linearly with pulse rate and were more effective at higher pulse rates. TFL operation time and ablation rates were found to be more efficient than for Ho:YAG. TFL vapor bubbles were discovered to collapse multiple times along the optical axis of the fiber, while the Ho:YAG laser created a single, larger, bubble that collapsed only once. Due in part to these differing bubble dynamics, lower pressures were observed with the TFL. Every experiment was designed to examine the TFL ablation mechanisms and find optimum laser parameters to safely increase stone ablation rates and efficiency.